Peculiarities of calculating the cyclic strength of important threaded joints - Leonavičius, Mindaugas; Krenevičius, Algimantas; Stupak, Stanislav; Šukšta, Marijonas (Journal of Civil Engineering and Management, 2002)
The calculation of the strength of important threaded joints is started by defining the minimum size of the cross-section of bolts (studs). Then the static and cyclic strength is tested. The studs of the demountable joints of nuclear power equipment are calculated in accordance with the norms of the Russian Federation and the ASME Code. The calculation methods coincide in essence, they are based on similar limit states; however, there also some differences exist. The authors investigate and compare both methods in their work. There is a brief analysis of calculation methods in the article. For closer definition of standards and their substantiation the authors used experimental and theoretical investigations performed at Laboratory of Strength Mechanics of Vilnius Gediminas Technical University. In order to develop a uniform cyclic strength and shakedown calculation procedure for critical threaded joints, a completely new calculation of a progressive profile change is recommended to be performed before the calculation of cyclic strength. The results have been used in the development of calculation standards for nuclear power equipment, in designing mineral grinding machines and evaluating their residual resource. Article in Lithuanian. First Published Online: 30 Jul 2012